Towards a new national sustainable development strategy – findings of in-depth interviews - Karcagi-Kováts, Andrea (Acta Agraria Debreceniensis, 2012)
Hungary’s new national sustainable development strategy is expected to be drawn up by 2012 and social debate for discussion has already been under way. This document provides the basis of all other strategies, programs and plans. I prepared a survey by the method of structured in-depth interviews to explore the opinion of experts engaged in environmental issues and strategy development about sustainable development, the situation of the Hungarian strategy adopted in 2007 and applied indicators. The picture is highly diverse: there is a lack of unified viewpoint even about the concept of sustainability. However, the definition of a common, jointly adopted concept is the first stage in strategy development. Precisely formulated objectives and their related indicators are required for a strategy to fulfill its role – this is the theoretical part of strategic thinking.